Treatment of Pulmonary Embolism: a Decade of Experience - A. Nikonenko; A. Nikonenko; S. Matvieiev; V. Osaulenko; S. Nakonechniy (Ukrainian Journal of Cardiovascular Surgery, 2019)
Pulmonary embolism (PE) is a major life-threatening illness which remains one of the main causes of sudden death throughout the world. The analysis of diagnosis and treatment of 472 patients with acute pulmonary embolism for a period of 10 years was performed. High efficiency of diagnosis using multispiral computer angiopulmonography (MSCT APG) has been established, thus this method completely supersedes the traditional selective angiopulmonography.Seventeen (3.6 %) patients died due to PE recurrence, another 8 (1.7 %) patients died due to the bleeding after using fibrinolytics and anticoagulants, and 14 (2.9 %) died due to progression of organs failure. This emphasizes the need to improve measures aimed to prevent PE recurrence and identify sources of possible bleeding and refrain from aggressive fibrinolytic therapy.The use of differentiated approach to the treatment with thrombolytic therapy and anticoagulants enabled to achieve recovery in 433 (91.7 %) patients who were discharged for outpatient treatment. New oral anticoagulants were prescribed to 94 (21.7 %) patients after discharge.